Estilo de vida y probabilidad de reflujo gastroesofágico en choferes de la Cooperativa de Transportes Santa de la ciudad de Loja - Hidalgo Chuquimarca, Katherine Paola (2024)
The term "lifestyle" encompasses a set of consciously and voluntarily practiced attitudes and behaviors by individuals. It has been noted that adopting unhealthy lifestyles can result in adverse health effects, including the onset of various diseases such as gastroesophageal reflux, which is defined as the passage of contents from the stomach to the esophagus. This study aimed to assess lifestyle patterns, determine the likelihood of developing gastroesophageal reflux based on age and gender, and establish the relationship between these variables among drivers affiliated with the Santa Transport Cooperative in the city of Loja from June to December 2022. The research employed a quantitative approach utilizing a cross-sectional cohort design, with a sample size of 75 participants. The FANTASTIC questionnaire was administered to evaluate lifestyle, while the Gastroesophageal Reflux Disease Questionnaire (GERD-Q) was employed to assess the likelihood of gastroesophageal reflux development. Findings revealed that among females, 33.33% (n=2) and 37% (n= 37) of females exhibited good lifestyle habits, respectively. 53.62% (n=37) of males exhibited good lifestyles habits, individuals aged 20- 40 demonstrated a lower risk of gastroesophageal reflux, with 40.58% (n=28) exhibiting such tendencies, while females within the 18-34 age group exhibited a moderate likelihood at 50.00% (n= 3). Notably, 33.33% (n=25) of the population demonstrated both good lifestyle practices and a reduced probability of developing gastroesophageal reflux. Upon conducting Spearman correlation analysis, indicates a non-lineal correlation, with p=0.216. It is concluded that there is a predominance of a good lifestyle with a medium probability of low risk of gastroesophageal reflux. Finally, it is recommended that participants, together with occupational health, work to promote healthy lifestyles and to the further research with a larger and more diverse sample over an extended duration is warranted to ascertain more robust conclusions